PENGARUH AKTIVITAS RUMAH TANGGA TERHADAP POTENSI TERJADINYA CARPAL TUNNEL SYNDROME - Eka Yusmanisari; sulis tia ningsih; Roy Virmanda (IFI cabang Kota Bekasi, 2023)
Carpal Tunnel Syndrome (CTS) is a syndrome that occurs due to the median nerve being compressed in the carpal tunnel in the wrist. Housework that is done every day has the potential to cause carpal tunnel syndrome because household work is done repeatedly or continuously every day. To broaden the knowledge of the Ngempeng Bangil community, the author submits a community service proposal with the title The Influence of Household Activities on the Potential for Carpal Tunnel Syndrome (CTS) in the Elderly in Ngempeng Bangil Village. Physiotherapy service activities for the elderly community in Ngempeng Bangil Village on Friday, 17 March 2023 can be implemented smoothly, orderly and on time. This activity was attended by approximately 40 people. Carpal Tunnel Syndrome (CTS) is a syndrome that occurs due to the median nerve being compressed in the carpal tunnel in the wrist. In the elderly in Ngempeng Bangil Village, Arbain Housing, there are 20% of elderly people who are positive for Carpal Tunnel Syndrome. The services used in this activity are cholesterol tests, uric acid tests, tinel tests, phallen tests and starching exercises at young joins.